Female sweet-likers have enhanced cross-modal interoceptive abilities. (1st October 2021) - Iatridi, Vasiliki; Quadt, Lisa; Hayes, John E.; Garfinkel, Sarah N.; Yeomans, Martin R.
Abstract: There are well known phenotypic differences in sweet-liking across individuals, but it remains unknown whether these are related to broader underlying differences in interoceptive abilities (abilities to sense the internal state of the body). Here, healthy women ( N  = 64) classified as sweet likers (SLs) or sweet dislikers (SDs) completed a bimodal interoception protocol. A heartbeat tracking and a heartbeat discrimination task determined cardiac interoception; both were accompanied by confidence ratings. A water load task, where participants consumed water to satiation and then to maximum fullness was used to assess gastric interoceptive abilities. Motivational state, psychometric characteristics and eating behaviour were also assessed. SLs performed significantly better than SDs on both heartbeat tasks, independently of impulsivity, anxiety, depression, and alexithymia. No differences in metacognitive awareness and subjective interoceptive measures were found. With gastric interoception, SLs were more sensitive to stomach distention, and they ingested less water than SDs to reach satiety when accounting for stomach capacity. SLs also scored higher on mindful and intuitive eating scales and on emotional eating particularly in response to negative stimuli; emotional overeating was fully mediated via interoceptive performance. Overall, our data suggest the SL phenotype may reflect enhanced responsiveness to internal cues more broadly.